2023
DOI: 10.3390/nu15030551
|View full text |Cite
|
Sign up to set email alerts
|

Improved HDL Cholesterol through Vitamin D Status Correction Substantially Lowers 10-Year Atherosclerotic Cardiovascular Disease Risk Score in Vitamin D-Deficient Arab Adults

Abstract: This interventional study aimed to determine whether correcting vitamin D status in deficient Arab adults [25(OH)D <50 nmol/L] improves their 10-year risk of Atherosclerotic Cardiovascular Disease (ASCVD) risk scores. Saudi adults (58 males 62 females) with baseline vitamin D deficiency (<50 nmol/L) were given 50,000 IU cholecalciferol weekly for 2 months, then twice a month, followed by daily 1000 IU until month 6. Fasting blood samples were collected pre- and post-intervention and assessed for glucose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
1
17
0
1
Order By: Relevance
“…VD supplementation is considered one of the most effective ways to improve the lipid profile. One prospective study found that VD supplementation over 12 months increased HDL cholesterol levels among adults, consequently reducing the atherosclerotic cardiovascular disease risk score [45]. Furthermore, a consistently positive correlation between VD status and HDL-C is in accordance with several observational studies conducted with children [46].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…VD supplementation is considered one of the most effective ways to improve the lipid profile. One prospective study found that VD supplementation over 12 months increased HDL cholesterol levels among adults, consequently reducing the atherosclerotic cardiovascular disease risk score [45]. Furthermore, a consistently positive correlation between VD status and HDL-C is in accordance with several observational studies conducted with children [46].…”
Section: Discussionsupporting
confidence: 72%
“…This finding supports many hypotheses that VD will increase or regulate good cholesterol, especially in males, who are at higher risk for CVD and heart disease. We have previously observed that VD status correction among VD deficient Saudi adults corresponds to a substantial reduction in atherosclerotic cardiovascular disease [45] since they do not have a high level of estrogen, as women do. Higher levels of estrogen in premenopausal women have been found to increase levels of HDL; thus, women are much less susceptible to coronary heart disease (CHD) and other atherosclerotic diseases compared to men [46,47].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a very recent interventional study, the correction of vitamin D deficiency in Arab adults seemed to improve their 10-year risk of atherosclerotic cardiovascular disease (ASCVD). This result is very interesting; once optimal vitamin D levels were achieved, there was a modest improvement in glucose and HDL-C levels, resulting in a decrease in ASCVD risk scores [ 112 ]. However, a study by Schwetz et al demonstrated that vitamin D supplementation significantly increased TC, TGs, VLDL-C, LDL-C, HDL-C, ApoB, and ApoB, indicating a negative effect on lipid profile [ 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent vitamin D supplementation trial conducted in KSA involving 120 participants of whom 32 had 25(OH)D concentrations <10 ng/mL and 88 had 25(OH)Ds between 10 and 20 ng/mL [ 82 ]. Those in the treatment arm were given 50,000 IU/week vitamin D 3 for two months, then twice a month, followed by daily 1000 IU until month 6, while those in the control arm were given a placebo.…”
Section: Cardiovascular Diseasementioning
confidence: 99%